Determine the functional and radiological outcome of T3 proximal femur nail in the treatment of intertrochanteric fracture of femur - Paneliya, Manan B.; Shetty, Sunil H.; Chand, Kumar Abhineet; Sharma, Vidur (International Journal of Research in Orthopaedics, 2022)
Background: T3 is the new generation nail used for fixation of intertrochanteric fractures. The lag screw is designed to transfer the load of the femoral head into the nail shaft by bridging the fracture line to allow fast and secure fracture healing. The load carrying thread design of the T3 lag screw provides large surface contact to the cancellous bone, this provides high resistance against cut out. Methods: 30 subjects attending the study were operated with T3 proximal femur nail in the treatment of intertrochanteric fracture of femur. Prospective, randomised case-controlled study done over period of 1 year. Results: Significant results were obtained while comparing the mean RUSH score and mean Harris hip score at different postoperative follow-up time intervals with good to excellent outcome and less operative time and low complications rate. Conclusions: T3 is the new generation nail used for fixation of intertrochanteric fractures and is a dependable implant for the fixation. It has good to excellent outcomes and takes less operative time with low complication rates. The anatomical shape of the nail is universal for all indications involving the treatment of intertrochanteric fractures. The load carrying thread design of the T3 lag screw provides large surface contact to the cancellous bone, thus providing high resistance against cut out. The set screw prevents rotation of the lag screw. The T3 has a single screw passing into the neck of the femur and its Set Screw that is passed into the proximal part of the femoral nail sits into the groove of the Lag screw, thus providing rotational stability.